Kinerja Keuangan Pemerintah Provinsi Daerah Khusus Ibukota Jakarta (Studi Pada Badan Pengelola Keuangan Daerah Provinsi Daerah Khusus Ibukota Jakarta Tahun Anggaran 2011-2013) - Prasetyo, Muhammad Agung (Jurnal Administrasi Publik, 2015)
Abstract: The Financial Performance of Jakarta Province Governmental (Study at Local Government Finance Office of Jakarta Province, Fiscal Year 2011-2013). The financial performance of Local Government is a part of financial target acomplishment which is assessed by the result of accountability in order to run Local Government Budget toward financial ratio. Based on Government Regulation Number 71 Year 2010 about Standart of Governmental Accounting, explained by showing the information related income, expenditure, and regional financing in order to measure the financial performance of local government. This research used descriptive by qualitative approached. The result showed that the income financial performance of Jakarta Province is good categorized by seeing from financial independent which is included in participatory category. The average of financial effectiveness is amounted to 106,32%, financial efficiency is amounted to 49,99% in average, tax revenue is amounted to 84,27% which is give a big contribution in local revenue. However, local income growth still decrease in every year. Based on expenditure performance aspect, Jakarta Province still prioritize expenditure allocation toward operation expenditure which is amounted to 72,17% in average, meanwhile the equity expenditure is amounted to 27,82% during 2011 till 2013. Based on local financing performance aspect have showed budget surplus with total regional of revenue, regional expenditure, and unspent funds at end of fiscal year showed fluctuative. Keywords: financial performance, local financial management, local government budget (APBD). Abstrak: Kinerja Keuangan Pemerintah Provinsi Daerah Khusus Ibukota Jakarta (Studi pada Badan Pengelola Keuangan Daerah Provinsi Daerah Khusus Ibukota Jakarta Tahun Anggaran 2011-2013). Merupakan tingkat pencapaian target keuangan, dinilai melalui hasil pertanggungjawaban pelaksanaan APBD terhadap rasio-rasio keuangan. Peraturan Pemerintah Nomor 71 Tahun 2010 tentang Standar Akuntansi Pemerintahan menjelaskan bahwa untuk mengukur kinerja keuangan pemerintah perlu diinformasikan terkait pendapatan, belanja, dan pembiayaan daerah. Jenis penelitian ini adalah deskriptif dengan pendekatan kualitatif. Hasil penelitian menunjukkan, kinerja keuangan pendapatan tahun 2011-2013 dinilai baik, rasio kemandirian keuangan tergolong dalam pola hubungan partisipatif, rasio efektivitas 106,32%, rasio efisiensi 49,99%, kontribusi penerimaan pajak 84,27%. Aspek pajak inilah memberikan kontribusi terbesar dalam penerimaan pendapatan daerah, sedangkan laju pertumbuhan pendapatan masih mengalami penurunan setiap tahunnya. Dari aspek kinerja belanjanya, sejak tahun 2011-2013 diprioritaskan ke dalam belanja operasi dengan rata-rata 72,17%, sedangkan rata-rata belanja modal hanya 27,82%. Dari aspek kinerja pembiayaan, terjadi surplus dengan jumlah pendapatan, belanja, dan SILPA fluktuatif. Kata kunci: kinerja keuangan pemerintah, pengelolaan keuangan daerah, APBD.